2019
DOI: 10.1021/acsami.9b16822
|View full text |Cite
|
Sign up to set email alerts
|

Is Charge-Transfer Doping Possible at the Interfaces of Monolayer VSe2 with MoO3 and K?

Abstract: Being a metallic transition-metal dichalcogenide, monolayer vanadium diselenide (VSe2) exhibits many novel properties, such as charge density waves and magnetism. Its interfaces with other materials can potentially be used in device applications as well as for manipulating its intrinsic properties. Here, we present a scanning tunneling microscopy and synchrotron-based X-ray photoemission spectroscopy study of the surface charge-transfer doping using efficient electron-withdrawing and electron-donating material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The main reason is that the amorphous region decreases with the increase of crystallinity, the chain segment molecules are closely arranged, the movement of molecular chain is blocked, thus, T g,PLA increases. [50] Figure 7a,b shows that, for all the samples tested, the PLA/ TPU blends showed a change from brittle fracture to ductile fracture with decreasing of the tensile strength and modulus, by the addition of a soft TPU phase in the PLA matrix. From Figure 7a, we also found that the FDM specimen shows a gradual fracturing phenomenon with a lowered elongation at break than that of the IM samples.…”
Section: Compatibility and Crystallization Analysismentioning
confidence: 98%
“…The main reason is that the amorphous region decreases with the increase of crystallinity, the chain segment molecules are closely arranged, the movement of molecular chain is blocked, thus, T g,PLA increases. [50] Figure 7a,b shows that, for all the samples tested, the PLA/ TPU blends showed a change from brittle fracture to ductile fracture with decreasing of the tensile strength and modulus, by the addition of a soft TPU phase in the PLA matrix. From Figure 7a, we also found that the FDM specimen shows a gradual fracturing phenomenon with a lowered elongation at break than that of the IM samples.…”
Section: Compatibility and Crystallization Analysismentioning
confidence: 98%
“…The use of nucleating agents in the form of mineral fillers can promote the formation of the crystalline phase and at the same time confer additional thermal resistance to the biodegradable polymer. [31][32][33][34] Alternatively, the introduction of advanced polymers, featuring higher heat resistance, [35][36][37][38][39] inside the blend, can represent another viable strategy. In all cases, any strategy chosen for the resolution of the aforementioned issues must satisfy the restrictions related to compostability of the material.…”
Section: Introductionmentioning
confidence: 99%
“…These coatings demonstrate excellent super-hydrophobicity due to decreased spacing between micro/NP spherical features at their surface. At the concentration of 10%, all PDMS-POSS coatings exhibited excellent super-hydrophobicity regardless of the numbers of sprays (1)(2)(3)(4). The water contact angle on these coatings was in the range of 159-164.4° while the sliding angle was in the range of 2.58-1.94°.…”
Section: Wettabilitymentioning
confidence: 97%
“…No material was yet found to be truly icephobic, i.e., being able to prevent attachment of ice. Hence, large research effort is directed toward development of effective anti-icing coatings [1][2][3][4][5][6][7] due to rapidly growing demand for protection of engineering structures www.advancedsciencenews.com www.particle-journal.com microspheres [18][19][20][21][22][23][24][25][26][27] are difficult, time consuming, and costly, and consequently they cannot be flexibly used as in situ processes in a broad range of industrial domains such as on-site application of anti-icing and other functional coatings onto existing engineering structures.…”
Section: Introductionmentioning
confidence: 99%